Prevalence of self-care practices and assessment of their sociodemographic risk factors among diabetes in the urban slums of Bengaluru - Dasappa, Hemavathi (J Family Med Prim Care, 2017)
OBJECTIVE: The objective of this study was to determine the prevalence of self-care practices in the urban slums of Bengaluru among diabetes and also to assess their sociodemographic risk factors. MATERIALS AND METHODS: A cross-sectional study was done in the two slums of Bengaluru comprising 163 diabetes patients. The prevalence of self-care practices and their sociodemographic risk was analyzed. RESULTS: Maximum adherence was seen for blood sugar testing (77.91%), and least adherence was seen for diet (12.26%). Adherence to exercise was 30.67%, adherence to foot care was 48.46%, and adherence to medication was 60.73%. Some of the sociodemographic factors associated with good self-care practices are young age, gender, formal education, occupation, and religion. Good adherence to medication is associated with better control of blood sugars. CONCLUSION: A clinician should be able to identify these risk factors and give special attention to these groups of patients and make realistic recommendations for self-care activities.